Are parents' working patterns associated with their child's sleep? An analysis of dual-parent families in Australia - Magee, C; Iverson, D; CaputI, P (My University, 2011)
Insufficient sleep in children predicts emotional and behavioral problems, poorer school performance, and health problems. Child sleep durations have declined in recent decades, suggesting a need to identify and understand predictors of short sleep. The present study investigated whether aspects of parental employment (i.e. parental work hours, and non-standard work hours) were associated with sleep in children. Data collected from 2477 children aged 6–7 years as part of the Longitudinal Study of Australian Children were used in this paper. Child sleep duration, bedtimes, and wake times were determined from parent self-report using time-use diaries. Parents completed a survey assessing their work patterns as well as a range of other demographic and social factors. The results indicated that long mother work hours were associated with later bedtimes and increased odds of <9.5 h sleep in children. Long father work hours were associated with earlier waketimes, earlier bedtimes, and reduced odds of long sleep. Non-standard work hours were associated with longer sleep and earlier bedtimes. The present results indicate the need to develop strategies to limit any adverse effects of parental work on child sleep, perhaps by promoting earlier and regular bedtimes. These findings warrant further investigation given the importance of sleep in healthy child development.
Keywords: Employment -- Hours; Child Development -- Sleep; Labour market; Childhood and child development; Child Development; Employment; Hours; Sleep; Childhood and child development; Employment and unemployment